Air-Liquid Exchange by Free Hand and One Needle for Unhealed Macular Hole - Haishuang Lin; Yiting Ji; Luqi Xia; Bo Lin; Zhihua Li; Zhixiang Hu; Ronghan Wu (Journal of Ophthalmology)
Aim. To report the treatment of 7 cases of unsealed hole after macular hole surgery with air-fluid exchange. Methods. Retrospective case series. We collected 7 eyes of 7 patients with unsealed hole an unsealed hole about 2 weeks after macular hole surgery (23G vitrectomy with internal limiting membrane peeling with sterilizing air tamponade) in our hospital from February 2018 to December 2018. All patients underwent “air-liquid exchange by free hand and one needle.” The prone position was taken one week after operation. The macular holes before and after operation were examined by frequency-domain optical coherence tomography (SD-OCT). Results. The size of the macular hole before vitrectomy was 481 ± 156 μm (range: 281–609 μm). Two weeks after vitrectomy (before air and liquid exchange), the size of the macular hole was 295 ± 92 μm (range: 210–421 μm). All macular holes were closed within 7–14 days after air-liquid exchange. There was no complaint of discomfort among these patients. Conclusion. From this preliminary study, air-liquid exchange by free hand and one needle seems to be safe and effective in the treatment for patients with unsealed and tiny macular hole after vitrectomy as the lack of long effective gas in China. However, the exact efficacy and safety need further large case studies.